Effects on accounting legislation by an EU-wide implementation of the IFRS for SMEs – the case of Germany - Meyer, Corinna (Riga Graduate School of Law, 2020)
Harmonisation of companies’ financial reporting obligations is essential to economic decision-making in an international business environment. The degree of harmonisation for small and medium-sized entities (SMEs) is still relatively low but the acceptance for the IFRS for SMEs is increasing in recent years. Currently, the standard is being revised and its standard-setting body is awaiting comments from its stakeholders. While the European Union is reluctant to adopt the IFRS for SMEs, the success of its internal harmonisation attempts by the EU Accounting Directive is doubtful and often criticised by the Directive’s stakeholders and researchers. The excessive number of options led to 27 different accounting systems and left the comparability of small and medium-sized entities’ financial statements across the Union flawed. This thesis aims to provide a theoretical background for a harmonised regulatory framework for SMEs’ financial reporting obligations, to identify significant incompatibilities between the IFRS for SMEs and EU accounting legislation as well as national accounting legislation of Germany, and to recommend legislative changes necessary for an EU-wide IFRS for SMEs implementation – on EU level and Member State level demonstrated at the case of Germany. The research is based on methods of legal and comparative analysis using primary and secondary sources of law, scientific literature, official documents and websites. The main findings reveal that the harmonisation of accounting legislation for SMEs can be significantly improved by the implementation of IFRS for SMEs in the EU. The author suggests that, at the outset, the most appropriate way of implementation would be a "permission to apply", i.e. a discretionary choice for SMEs to apply the standard. For this purpose, the provisions on the following accounting topics in the EU Accounting Directive need to be changed: extraordinary items, measurements of financial instruments, the useful life of goodwill, recognition of negative goodwill, and presentation of unpaid called-up subscribed capital. The necessary changes in the German legislation depend on the current use of the Directive’s Member State Options and must be implemented in the Commercial Code.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::European law; Research Subject Categories::LAW/JURISPRUDENCE::Private law::Commercial and company law; Research Subject Categories::LAW/JURISPRUDENCE::Financial law